Evaluation of modified potato starch in diets for the early-weaned pig - Kerr, C.A.; Richert, B.T.; Bergstrom, J.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two growth trials were conducted to compare the effectiveness of replacing either corn or lactose with modified potato starches in diets for conventionally and early-weaned pigs. In Exp. 1, 198 pigs (initially 9.4lb and 19 d of age) were used to determine if modified potato starch (potato starch 1) can replace a portion of the lactose in a high nutrient dense diet. Pigs were allotted by weight, gender, and ancestry to each of six dietary treatments with either five or six pigs per pen and six pens per treatment. The control diet contained 10% dried whey (7.2% lactose), 7.5% spray-dried porcine plasma, 2.5% select menhaden fish meal, and 1.75% spray-dried blood meal. Additional treatments were formulated by adding 7 or 14% modified potato starch or lactose in place of com. A positive control diet also was formulated containing 29% dried whey (providing the same amount of lactose as the 10% dried whey plus 14% lactose diet). All diets were formulated to contain 1.5% lysine, and .90% Ca, .80% P, and 17.88% soybean meal and were fed in a meal form. From day 0 to 14 postweaning, increasing dietary lactose tended to linearly improve ADG and ADFI. Added potato starch did not improve ADG compared with pigs fed the control diet, but ADFI increased linearly with increasing potato starch. In Exp. 2, 180 pigs (8.5 lb and 14 d of age) were used to evaluate the effects of two modified potato starches (potato starch 1 or potato starch 2,a further hydrolyzed potato starch with a greater percentage of sugars as either glucose or maltose as a replacement for either com or lactose in a segregated early-weaning diet (SEW). Pigs were fed a control diet containing 15% dried whey, 12% added lactose, 6% porcine plasma, and 6% select menhaden fish meal. Modified potato starch 1 or 2 (12 %) replaced either corn or the added lactose on an equal weight basis. From d 0 to 7 postweaning, pigs fed the modified potato starch 1 had greater ADG and ADFI than those fed modified potato starch 2. Pigs fed diets with either starch substituted for corn had greater ADG than those fed diets with either starch substituted for lactose. From d 0 to 14 and d o to 21, pigs fed diets containing either modified potato starch substituted for corn tended to have greater ADG than those fed the control diet. This appeared to be the result of greater feed intake of pigs fed the diets containing either starch substituted for corn compared with those fed the control diet or diets containing either starch substituted for lactose. Pigs fed diets with either modified starch substituted for lactose had similar ADG as those fed the control diet. In conclusion, these results suggest that potato starch can improve growth performance of pigs when substituted for corn and can replace a portion of the lactose in an SEW diet without adversely affecting performance.
Keywords: Swine; Modified potato starch; Early-weaned pig